Fluvial or aeolian grains? Separation of transport agents on Mars using earth analogue observations. (15th November 2018) - Kapui, Zs; Kereszturi, A.; Kiss, K.; Szalai, Z.; Újvári, G.; Hickman-Lewis, K.; Foucher, F.; Westall, F.
Abstract: The particle size, shape, surface texture and composition of aeolian and fluvial sedimentary samples were analyzed and compared using optical microscope-based automatized image analysis, in order to suggest indicators that could discriminate these two modes of transport on Mars. The principal goal is to assess if such indicators – established on Earth – could be used on Mars thereby aiding interpretations on the origin of sediments analysed by the ExoMars 2020 rover during its mission. Wind and water transported sand from, respectively, the Sahara Desert and the Maros river bar in Hungary were investigated and treated as mainly aeolian and fluvial end-members. In addition, two Mars-analogue aeolian and fluvial basaltic sediments from Iceland were analysed similarly. Our analyses demonstrated that useful parameters for the distinction of aeolian and fluvial transport included the degree of sorting, the grain diameter/perimeter ratio, the circularity (reflecting the sphericity of the grains) and convexity (showing roughness of the grains) of particles. Mature aeolian sands are always well-sorted with high diameter/perimeter ratios since they are dominated by rounded grains. Differences were observed in both surface textures and the range of mineral compositions, wherein the aeolian samples reflect a more mature state. Separation of the two Icelandic samples with different origins was less straightforward due to both shorter transport distances and the fact that the fluvial sample was made of scoria, although the intermixing of grains with a probable aeolian origin could be also determined. The characteristics of grain size and shape parameters are potential indicators allowing the separation of the two transport modes, and their determination is shown to be feasible based on high resolution Close-UP Imager (CLUPI) observations. Nonetheless, knowledge of the geological context – for instance sedimentary facies, layering, sorting of the sediments and grain shape – is a requirement for proper interpretations. These sedimentary features could be party determined by MaMISS, CLUPI and PanCam observations. Differences between aeolian and fluvial grains are expected to be more pronounced on Mars than on Earth due to the episodic and likely short-term subaqueous transport, as opposed to the long-term activity of wind. However, future interpretations of the ExoMars 2020 rover images of martian sedimentary grains will be hampered by the limited knowledge of fluvial/aeolian transport on Mars. Based on our results, future research should focus on determining the dominant transport mode of any sediment and the degree of grain mixing, which strongly based on the transport mode. Highlights: Mars-analogue particulate sediments, including basaltic in origin were analyzed. Morphometric differences in the shapes of aeolian and fluvial grains were identified. The ExoMars CLUPI camera will be able to distinguish the agents of deposition for grains of 100–200 μm size. Aeolian grains are expected to be more mature, and differ from fluvial grains on Mars. Local sedimentary features give important context information to assist the identification of grain origin.